The New Pocket Rogets Thesaurus in dictionary form / Norman Lewis - Lewis Norman (New York (State)/ WSP, 1967)
Roget's New Pocket Thesaurus In Dictionary Form is bigger, easier to use, and more legible than any other paperback thesaurus. The short lines of the two-column type pages make it the most efficient tool you can use. Divided into more than 1,000 categories, each one explains an idea in depth, each is arranged both by parts of speech and by logically associated facets of meaning. Both individual entries and major categories of meaning are thoroughly cross-indexed. This indispensable reference work will help give you a new mastery of spoken or written English, whether used at home, in the office, in school, or in college.
1. Palabras desconocidas en Inglés
Col. Ref
Keywords: 1. ADJUNCT ASSISTANT PROFESSOR OF ENGLISH 2. DIVISION OF GENERAL EDUCATION